Interactive Videogame Versus Core Stability Exercises On Postural Control In Female Patients With Overweight - El Sayed, Shimaa G.; Mohamed Ali, Aya Fawzy; Elmasry, Haitham M.; Eraky, Zeezy S.; El-Din, Sara S.; Abdelaziz, Amira Hassan; El Sayed, Dalia Galal (International Journal of Aquatic Research and Environmental Studies, 2026)
Background: Obesity is a chronic, neurobehavioral disease influenced by genes and environmental factors affecting brain development. Purpose: The purpose of this study is to compare the effects between videogame exercises and core stability exercises on postural control dysfunction in female patients with overweight. Methods: Forty patients (women) aged 40-60 years with body mass index over 25 were randomly assigned into the following two groups. Group (A) received the Wii fit balanced exercises for three times per week for four weeks as total treatment duration in form of (Ski Slalom, Advanced Skiing, Ski Jumping followed by Header and Jump Rope).; Group (B) received core stability exercises for 4 weeks (3times/week) in form of 1. Supine bridge (3 sets x 10 repetitions x 10 second holds), 2. Curl up (3 sets x 10 repetitions), 3. Supine unilateral bridge (3 sets x 10 repetitions for each leg x 10 second holds), 4. Abdominal crunching (10 repetitions x 10 second holds), 5. Plank (3 sets x 10 repetitions) and 6. Bird dog (3 sets x 10 repetitions for each limb). Results: The between-group analysis showed significant improvement in group A after treatment (p
Keywords: Core stability exercises; Overweight; Videogame.